G32 An evaluation of a complex simulated clinical shift scenario with final year undergraduate children's nursing students. (27th April 2015) - Clarke, D; Davies, J; Nathan, M
Abstract : Background: The last decade has witnessed the emergence of simulation as a useful, but some times challenging teaching methodology. This is supported by a number of sources of evidence, which focus strongly upon student evaluation of the learning experience. The challenges are equally worth consideration. These include issues such as the commissioning of space and staff expertise in resourcing and creating a situation which is as close to real practice as possible. Aims: To explore the use of a complex simulated scenario with third year children's nursing students. To share the process of educational evaluation that was undertaken. To share the results of this educational intervention. Methods: Children's nursing students were exposed to a complex simulated clinical shift. The activities included: managing the clinical area; the transfer of a sick child; managing a medication error; subsequent discussion with the parents; and prioritising and organising care. The use of role-play was utilised throughout, to create a realistic experience and the simulation activity took place in two settings to enable the transfer of a child from one clinical area (the assessment unit) area to another (the ward). The simulation experience was undertaken at the end of the third year undergraduate program by three cohorts of students (n = 41). Following the experience, data were collected through a post-simulation de-briefing and a Likert style questionnaire, enabling the collection of qualitative and quantitative evaluation data concerned with the student's experience of the simulation. Results and conclusion: Overwhelmingly, the results showed that this was a positive experience for the students, demonstrating a number of perceived improvements in the application of their clinical skills. These included: development of specific management skills; enhanced confidence; development of self-awareness; and the transferability of skills to practice. Students also demonstrated strong agreement in terms of the realism of the experience.